2020
DOI: 10.1177/0269881120959617
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-195 predicts olanzapine response in drug-free patients with schizophrenia: A prospective cohort study

Abstract: Background: Disturbances of microRNA-195 have been implicated in the pathogenesis of schizophrenia. However, microRNA-195 levels in schizophrenia are controversial. Aims: To the best of our knowledge, this is the first study to examine microRNA-195 levels in untreated schizophrenia patients and their relationship to olanzapine response. Methods: We recruited 81 untreated schizophrenia patients and 96 healthy controls. The patients received 2 months olanzapine treatment. MicroRNA-195 levels in peripheral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…For instance, a previous study has revealed a significantly decreased level of miR-195 in peripheral blood mononuclear cells of patients responding to olanzapine treatment, although its level did not vary between drug-naïve schizophrenia patients and controls (Huang et al, 2021), and serum level of miR-21 was decreased following administration of antipsychotics (Chen S. D. et al, 2016). Moreover, both baseline level and reduction rate were positively correlated with reduction rate of positive and negative syndrome scale total scores (Huang et al, 2021). The function of lncRNAs has been appreciated in the pathogenesis of mental diseases including schizophrenia, bipolar disease, and depression, by dysregulating the expression of target genes, and some specific lncRNAs play an important role in the recovery of depressed patients with antidepressant therapy (Table 2).…”
Section: The Role Of Ncrnas In Schizophreniamentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, a previous study has revealed a significantly decreased level of miR-195 in peripheral blood mononuclear cells of patients responding to olanzapine treatment, although its level did not vary between drug-naïve schizophrenia patients and controls (Huang et al, 2021), and serum level of miR-21 was decreased following administration of antipsychotics (Chen S. D. et al, 2016). Moreover, both baseline level and reduction rate were positively correlated with reduction rate of positive and negative syndrome scale total scores (Huang et al, 2021). The function of lncRNAs has been appreciated in the pathogenesis of mental diseases including schizophrenia, bipolar disease, and depression, by dysregulating the expression of target genes, and some specific lncRNAs play an important role in the recovery of depressed patients with antidepressant therapy (Table 2).…”
Section: The Role Of Ncrnas In Schizophreniamentioning
confidence: 94%
“…Some of the miRNAs have been identified to be associated with treatment responsiveness and efficacy rather than the disease itself. For instance, a previous study has revealed a significantly decreased level of miR-195 in peripheral blood mononuclear cells of patients responding to olanzapine treatment, although its level did not vary between drug-naïve schizophrenia patients and controls ( Huang et al, 2021 ), and serum level of miR-21 was decreased following administration of antipsychotics ( Chen S. D. et al, 2016 ). Moreover, both baseline level and reduction rate were positively correlated with reduction rate of positive and negative syndrome scale total scores ( Huang et al, 2021 ).…”
Section: The Role Of Ncrnas In Schizophreniamentioning
confidence: 99%
“…At baseline and 4‐week follow‐up, PANSS was used to evaluate the severity of psychotic symptoms. The reduction rate in the PANSS score was calculated by the formula: ( T b − T a ) / T a × 100%, where T a is the score at baseline and T b is the score at follow‐up 38 . Patients were defined as responders when the reduction rate of the PANSS total score was more than 30% according to previous studies 39,40 …”
Section: Methodsmentioning
confidence: 99%
“…Nurses monitored adherence to olanzapine treatment. 38 Patients were defined as responders when the reduction rate of the PANSS total score was more than 30% according to previous studies. 39,40…”
Section: Study Proceduresmentioning
confidence: 99%